Multiple malignant tumors in a patient with familial chordoma, a case report - Nuttavut Sumransub; Paari Murugan; Shelly Marette; Denis R. Clohisy; Keith M. Skubitz (BMC, 2021)
Abstract Background Chordoma is a rare bone tumor that is typically resistant to chemotherapy and is associated with genetic abnormalities of the T-box transcription factor T (TBXT) gene, which encodes the transcription factor brachyury. Brachyury is felt to be a major contributor to the development of chordomas. Case presentation We describe a 67-year-old woman who developed an undifferentiated pleomorphic sarcoma in her thigh. Despite treatment with standard chemotherapy regimens, she had a rapidly progressive course of disease with pulmonary metastases and passed away 8 months from diagnosis with pulmonary complications. Her medical history was remarkable in that she had a spheno-occipital chordoma at age 39 and later developed multiple other tumors throughout her life including Hodgkin lymphoma and squamous cell carcinoma and basal cell carcinoma of the skin. She had a family history of chordoma and her family underwent extensive genetic study in the past and were found to have a duplication of the TBXT gene. Conclusions Brachyury has been found to associate with tumor progression, treatment resistance, and metastasis in various epithelial cancers, and it might play roles in tumorigenesis and aggressiveness in this patient with multiple rare tumors and germ line duplication of the TBXT gene. Targeting this molecule may be useful for some malignancies.